Tinjauan Hukum Ekonomi Syariah tentang Praktik Pembulatan Timbangan pada Jasa Pengiriman Barang (Studi Kasus Kantor POS Cabang Sumoroto) Tahun 2022 - Aisi, Okta (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2023)
This type of research is a qualitative research (field research) with a normative and sociological approach. The subjects and objects of this research are employees and consumers of the Somoroto Branch Post Office, for data collection instruments using interviews, documentation, and literature study. Apart from primary data, data is also obtained from secondary data which is then processed using editing, organizing, and analyzing techniques and analyzed using data reduction techniques (data reduction), data exposure (data display), and conclusion drawing or verification (conclusion drawing/verifying). ). The results of this study explain that: 1). The rounding mechanism between the Post Office and the Consumer is included in the Muamalah Madiyah category so that the agreement between the two parties uses a wage approach. The Post Office uses a PER-kg scale which is intended to make it easier to determine prices with a progressive and volumetric rounding system, this system is determined according to the type of goods to be sent by consumers and of course will affect the price to be paid. 2). A review of Islamic Economic Law on the rounding of the scales of goods delivery services at the Post Office is in accordance with Islamic Law due to a mutual agreement between the owner and the consumer. However, in technical terms, the implementation seems to be more in favor of the owner because it takes advantage of the rounding process and tends to harm consumers and the transaction contains Gharar because it is not transparent in providing information on the weight of the goods. So that the mechanism is not in accordance with the principle of muamalah because there is dissatisfaction from consumers.